IMPLEMENTATION OF AUGMENTED REALITY LEARNING MEDIA ON GEOGRAPHY SYMPTOMS TO IMPROVE GEOGRAPHY IN STUDENT SOCIAL SCIENCES - Sudrajat, Ajat; Darojat, Ojat; Sumiyati, Sri; Ningtyas, Lisa Dwi; Purwantiningsih, Ary (JURNAL SOCIUS, 2023)
Geography symptoms are one of the materials in lectures intended for elementary school teacher education students at the Open University. Not infrequently, students feel difficulty in understanding the lesson. To increase students' understanding of geographical phenomena, augmented reality learning media was developed to improve student learning outcomes in this material. This research is research on the development of instructional media with the help of experimental research to see the effectiveness of its application. The sample was 90 elementary school teacher education students at the Open University. The results show that augmented reality is proven effective in increasing student learning outcomes in geographic phenomena in social studies. It is recommended that lecturers who teach material on geographic phenomena use this augmented reality learning media to support learning.